HS-GC-IMS with sensory evaluation technique to analyze volatile flavor compounds of jujube flowers - Ren, Peixing; Dao, Ruirui; Wang, Lili; Muhammad, Noor; Sang, Yaxin; Liu, Mengjun; Zhao, Zhihui (Frontiers in Plant Science, 2025)
The combination of headspace gas chromatography-ion mobility spectrometry (HS-GC-IMS) and sensory evaluation technique was employed to detect and analyze the volatile organic compounds (VOCs) in jujube flowers at different developmental stages across various varieties, and to compare them with other plant flowers known for their characteristic aromas. A total of 65 volatile compounds were identified in jujube flowers at different stages. The aroma fingerprint analysis revealed 24 distinct aromas, with 14 aromas increasing in intensity from the bud stage to full bloom. Varieties such as Fuxiang, Dongzao, and Xingguang exhibited significantly stronger aromas at the flowering stage compared to other varieties. Additionally, sensory evaluation indicated a preference for the fragrance of jujube flowers among men. This study offers new insights into the development of jujube flower-based spices, highlighting their considerable potential and laying a foundation for further research on plant flower spices.